Analisis Proses Bisnis Penyimpanan Bahan Baku pada Divisi Material Control - Kramanandita, Ridzky; Oktavia, Devitha (Neolectura, 2023)
The process of storing raw materials in companies is still carried out conventionally, namely by record it using paper forms containing details of raw materials, the amount of incoming raw materials and outgoing raw materials. The next process is to recapitulate the data by typing it into the Microsoft Excel application. As a result, raw material stock calculations are not real time and the results of raw material stock data processing are less accurate. To find out in detail the existing problems, a business process analysis is needed which is outlined in the picture. The method used is field observation, while the tools used are BPMN (Business Process Modeling Notation). The result of this research is a model that describes business processes with standard notation that is easy to understand. With this model, it will be able to display the availability of raw materials, both incoming raw materials and outgoing raw materials, as well as overall raw material availability reports. The reports could be used by other related departments such as the Planning and Purchasing Division, thereby increasing efficiency in recapitulating raw material data and minimizing data errors regarding the availability of raw materials.